Case Study on Advanced Hoisting, Positioning, and Control Techniques for Non-Standard Pier Construction in the Quanli-Dongfeng Viaduct Project - Li Ming; Liu Wanping; Zhou Yijun; Huang Chengwei (E3S Web of Conferences, 2024)
This study, reliant on practical projects, conducts an in-depth analysis of key technologies amid the construction of prefabricated viaducts. The primary focus is on the integrated hoisting, positioning, and control techniques for the bridge abutments and pier columns, culminating in a proposal of an innovative integrated and prefabricated construction approach. This approach optimizes the construction process and methods by factoring in the structural characteristics of different types of pier columns and addressing construction challenges. Simultaneously, it underscores the significance of material selection, prefabricated component design, and innovative construction techniques. The study also explores on-site management and quality control strategies to ensure the efficiency and safety of the construction process. The research indicates that this approach significantly improves construction efficiency, reduces safety risks, and solidly guarantees structural quality. These findings offer crucial theoretical and practical guidance for advancing the industrialization, modularization, and innovative development of construction techniques in bridge construction. They contribute to the continual optimization of technical innovation and engineering practices in the field of bridge construction.